Selecting biodiversity management areas - Davis, F. W.; Stoms, D. M.; Church, R. L.; Okin, W. J.; Johnson, K. N. (Sierra Nevada Ecosystem Project: Final Report to Congress, vol. II, Assessments and scientific basis for management options, 1996)
Here we present and evaluate a conservation strategy whose objective is to represent all native plant communities in areas where the primary management goal is to sustain native biodiversity. We refer to these areas as Biodiversity Management Areas (BMAs), which we define as specially designated public or private lands with an active ecosystem management plan in operation whose purpose is to contribute to regional maintenance of native genetic, species and community levels of biodiversity, and the processes that maintain that biodiversity. Our purpose in this chapter is to explore opportunities for siting BMAs in the Sierra Nevada region. The strategic goal is to design a BMA system that represents all major Sierran plant community types, which we use as a coarse surrogate for ecosystems and their component species. We consider a community type to be represented if some pre-defined fraction of its mapped distribution occurs in one or more BMAs. We use a multi-objective computer model to allocate a minimum of new land to BMA status subject to the constraints that all community types must be represented, and that the new BMA areas should be located in areas of highest suitability for BMA status. Our purpose in this exercise is not to identify the optimal sites for a Sierran BMA system; instead it is to measure some of the likely dimensions of plausible, alternative BMA systems for the Sierra Nevada and to develop a rationale that would guide others in formulating such a system. Thus we examine a wide range of possible BMA systems based on different assumptions, constraints, target levels for representation, and priorities. If one ignores current land ownership and management designations and sets out to represent plant communities in a BMA system based on Calwater planning watersheds (which average roughly 10,000 acres in size), an efficient BMA system requires land in direct proportion to the target level, at least over the range of target levels examined in this study. In other words, it takes roughly 10% of the region to meet a 10% goal, and 25% of the region to meet a 25% goal. The pattern of selected watersheds is very different from the current distribution of parks and wilderness areas, which are concentrated at middle and high elevations in the central and southern portion of the range. Public lands alone are insufficient to create a BMA system that adequately represents all plant community types of the Sierra Nevada. Many of the foothill community types occur almost exclusively on private lands. Terrestrial vertebrates are reasonably well represented in a BMA system selected for plant communities. A BMA system selected for vertebrates alone, however, has little overlap with the one for plant communities. Areas selected by the BMAS model show only a modest amount of overlap with areas selected by other SNEP working groups as focal areas for conserving aquatic biodiversity or late successional/old growth forests. However, the BMAS model can be formulated to favor these areas with little loss of efficiency, especially in the northern Sierra.
Keywords: biodiversity management area, reserve selection, BMAS model, representation, Sierra Nevada, California